Investigation of the influence of the nucleon pairing force on the octupole deformation of uranium and thorium isotopes in the mean-field approximation - Tarasov, V.N.; Kuprikov, V.I.; Pilipenko, V.V.; Tarasov, D.V. (Problems of Atomic Science and Technology, 2023)
In the Hartree-Fock-Bogolyubov approximation and the axial symmetry of nuclei with Skyrm forces SkM∗, the properties of U with A = 220 – 232 and Th with A = 218 – 230 isotopes were calculated. In addition, the properties of U and Th near the neutron drip line A = 280 – 292 were calculated. Pairing of nucleons in nuclei is described by pairing forces of zero radius of action of a mixed type with different sets of pairing force constants. In our calculations, we used constrained conditions on the parameters of quadrupole β₂ and octupole β₃ deformations of nuclei. It is shown that for the considered U isotopes, as well as Th isotopes, the deformation of the β₃ nuclei strongly depends on the choice of the parameters of the nucleon pairing force. У наближенні Хартрі-Фока-Боголюбова та аксіальної симетрії ядер із силами Скірма SkM∗ проведено розрахунки властивостей ізотопів U з A = 220 – 232 і Th з A = 218 – 230. Додатково проведені розрахунки властивостей U і Th біля границі нейтронної стабільності A = 280 – 292. Спарювання нуклонів у ядрах описується силами спарювання нульового радіуса дії змішаного типу з різними наборами констант сил спарювання. У розрахунках використовувалися накладені умови на параметри квадрупольної β₂ і октупольної β₃ деформацій ядер. Показано, що для розглянутих ізотопів U, як і ізотопів Th, деформація ядер β₃ сильно залежить від вибору параметрів сили спарювання нуклонів.